Vitamin E and Mortality in Male Smokers of the ATBC Study: Implications for Nutritional Recommendations - Hemilä, Harri (Frontiers in Nutrition, 2020)
The Dietary Reference Intakes (DRI)-monograph (USA and Canada) states that the estimated average requirement (EAR) of vitamin E for men and women of any age is 12 mg/day, which further leads to the recommended dietary allowance (RDA) of 15 mg/day. The EAR value is based on in vitro hemolysis in young males; a surrogate endpoint without any shown validity. The EAR is then extrapolated to older individuals. The validity of the EAR of 12 mg/day is therefore questionable. The current study analyzed the association between dietary vitamin E intake and the effect of 25 mg/day of vitamin E supplement on mortality in male smokers aged 50-69 years in the Alpha-Tocopherol-Beta-Carotene (ATBC) Study. The effect of vitamin E supplement was estimated by Cox regression. Among participants who had dietary vitamin C intake of 90 mg/day and more, vitamin E supplement increased mortality by 19% (p = .006) in those aged 50-62 years, but decreased mortality by 41% (p = .0003) in those aged 66-69 years. No association between vitamin E supplement effect and dietary vitamin E intake was found in these two groups, nor in participants who had dietary vitamin C intake of less than 90 mg/day. This analysis of male smokers challenges the validity of the ‘average requirement’ of 12 mg/day of vitamin E for males aged 51 years and older. Trial registration: ClinicalTrials.gov identifier NCT00342992.